Relationship beginning and serendipity: insights from an Italian case study. Issue 3 (19th October 2015) - Perna, Andrea; Runfola, Andrea; Guercini, Simone; Gregori, Gian Luca
Abstract : Purpose: – The purpose of this paper is to propose evidence on the role of serendipity in business relationship. It concerns the understanding of the unplanned development of the relationship and the opportunities that may arise from taking serendipity as a "shaping" factor of relationship beginning. Design/methodology/approach: – The paper recurs to a longitudinal case study in the mechanical industry. In particular the development of the relationship between an Italian manufacturing company as supplier and a Chinese large customer is presented. Findings: – The case study highlights the role played by serendipity in the beginning and development of the business relationship between an Italian manufacturing company and a Chinese customer. Originality/value: – The main theoretical contribution of the paper is to point out how serendipity may affect business relationship development.